A Branch and Price Algorithm for the Multi-Period Single-Sourcing Problem - Richard Freling; H. Edwin Romeijn; Dolores Romero Morales; Albert P.M. Wagelmans (Tinbergen Institute, 1999)
In this paper we propose a Branch and Price algorithm for solving multi-periodsingle-sourcing problems. In particular, we generalize a Branch and Price algorithm thatwas developed for the Generalized Assignment Problem (GAP) to a class of convexassignment problems. We then identify an important subclass of problems, containing manyvariants of the multi-period single-sourcing problem (MPSSP), as well as variants of theGAP, for which we derive an efficient solution procedure for the pricing problem, acritical factor in the efficiency of the Branch and Price algorithm. We execute anextensive numerical comparison between the performances of the Branch and Price algorithmand the MIP solver of CPLEX for a particular variant of the MPSSP.
Keywords: 330; Beschaffung; Theorie